Whole-Genome Methylation Analysis of Phenotype Discordant Monozygotic Twins Reveals Novel Epigenetic Perturbation Contributing to the Pathogenesis of Adolescent Idiopathic Scoliosis - Liu, Gang; Wang, Lianlei; Wang, Xinyu; Yan, Zihui; Yang, Xinzhuang; Lin, Mao; Liu, Sen; Zuo, Yuzhi; Niu, Yuchen; Zhao, Sen; Zhao, Yanxue; Zhang, Jianguo; et al. (Frontiers in Bioengineering and Biotechnology, 2019)
Background: Adolescent idiopathic scoliosis (AIS) is a complex disease affecting a large number of teenagers, especially in female. This study reveals novel epigenetic perturbation to the pathogenesis of AIS. Methods: A female monozygotic (MZ) twin pair discordant for AIS were examined for whole-exome sequencing and epigenome difference. Sets of differentially methylated regions (DMRs) were validated using MethylTargetTM method in 20 AIS female patients and 20 healthy female controls. Results: Few exome difference but several potential DMRs were found between the MZ twins. We identified 313 hypermethylated DMRs and 397 hypomethylated DMRs respectively. Most of them were enriched in the MAPK and PI3K-Akt signaling pathway, which may contribute to the discordance of AIS. Several DMRs related to scoliosis gene were tested, and the NDN: TSS-DMR (chr15:23932133-23932304, Hg19) was confirmed in additional samples. The methylation level of this DMR was significantly higher in the AIS group than in the control group (p=0.04). Conclusions: We described the epigenome difference in an AIS female discordant MZ twin pair using Whole Genome Bisulfite Sequencing (WGBS). The NDN: TSS-DMR had higher methylation level in AIS, which can help elucidate the potential etiology of AIS.